Alterations of plasma magnesium, copper, zinc, iron and selenium concentrations and some related erythrocyte antioxidant enzyme activities in patients with Alzheimer’s disease - Vural, Huseyin; Demirin, Hilmi; Kara, Yusuf; Eren, Ibrahim; Delibas, Namik (Journal of trace elements in medicine and biology, 2010)
The aim of the present study is to evaluate the status of plasma essential trace elements magnesium (Mg), copper (Cu), zinc (Zn), iron (Fe) and selenium (Se) concentrations and their some related antioxidant enzyme activities, erythrocyte glutathione peroxidase (GPx), superoxide dismutase (SOD), and catalase (CAT) activities in patients with Alzheimer’s disease (AD). Fifty patients with AD and fifty healthy control subjects were included in this study. Plasma Cu and Zn concentrations by atomic absorption spectrometry (AAS), plasma Mg and Fe concentrations by spectrophotometric methods and plasma Se concentrations by graphite furnace AAS were determined. Erythrocyte GPx, SOD and CAT activities were measured by spectrophotometric methods. Plasma Mg, Cu, Zn, Fe and Se levels and erythrocyte GPx, SOD and CAT activities were found to be significantly lower in patients with AD compared with controls. These results suggest that alterations in essential trace elements and their related enzymes may play a role in the etiopathogenesis of AD. Also, there is a defect in the antioxidant defense system, which may lead to oxidative damage in patients with AD. The changes in antioxidant enzyme activities may be secondary to the alterations in their cofactor concentrations.